Lithium‐Ion Batteries: Tuning Anionic Redox Activity and Reversibility for a High‐Capacity Li‐Rich Mn‐Based Oxide Cathode via an Integrated Strategy (Adv. Funct. Mater. 10/2019). (5th March 2019) - Li, Qingyuan; Zhou, Dong; Zhang, Lijuan; Ning, De; Chen, Zhenhua; Xu, Zijian; Gao, Rui; Liu, Xinzhi; Xie, Donghao; Schumacher, Gerhard; Liu, Xiangfeng
Abstract : In article number 1806706, Xiangfeng Liu and co‐workers propose to tune the oxygen redox activity and reversibility in an Li‐rich Li1.2 Mn0.6 Ni0.2 O2 cathode by an integrated strategy involving Li2 SnO3 coating, Sn doping, and spinel phase combination. This synergy not only suppresses the lattice oxygen loss and improves the anionic redox activity and reversibility but also facilitates Li + migration, which enhances electrochemical performance.